Deformation Fields Measurement of Crack Tip under High-Frequency Resonant Loading Using a Novel Hybrid Image Processing Method - Hongli Gao; Zhaonian Zhang; Wei Jiang; Kaiyong Zhu; Ao Gong (Shock and Vibration)
A novel hybrid image processing method is proposed to obtain the crack tip location, crack propagation path, displacement, strain fields, and plastic zone size of crack tip region under high-frequency resonant loading in this paper. An ordinary CCD camera is used to collect a series of crack images on one side of the compact tension (CT) specimen; meanwhile, a high-speed digital camera is used to acquire a series of digital speckle images of the other side of the specimen under the loading conditions at regular time intervals. Digital image processing (DIP) method is used to determine the macroscopic crack position. Digital image correlation (DIC) method is applied to obtain the displacement, strain fields, and plastic zone size of crack tip region. The characteristic digital speckle images of one stress cycle are obtained by data fitting and image matching method. Accordingly, the displacement/strain fields of crack tip region within one stress cycle and the displacement and strain amplitude fields with different crack lengths are obtained and analyzed. The obtained results are compared with the measured results of ordinary methods and show a good match. The success of this method will help to obtain better insight into and understanding of the fatigue and failure behavior of metal material with mode I crack under high-frequency resonant loading.